Exploring the complex population structure and admixture of four local Hungarian sheep breeds - Ramírez-Díaz, Johanna; Bobbo, Tania; Guldbrandtsen, Bernt; Schönherz, Anna A.; Cozzi, Paolo; Kusza, Szilvia; Sahana, Goutam; Stella, Alessandra; Manunza, Arianna (Frontiers in Genetics, 2025)
The origin of sheep and their spread following domestication have been widely investigated using archaeology, genetics, and genomics. A thorough investigation of the genetic diversity of the breeds is key to providing useful information for conservation and breeding programmes. In Hungary, sheep farming contributes to the agricultural sector and national economy. It plays a crucial role in rural livelihoods, exports, and environmental management while also contributing to the national economy and preserving Hungary’s cultural and agricultural heritage through traditional breeds. This study aims to analyse the population structure and patterns of admixture in four local Hungarian sheep breeds, namely, Indigenous Tsigai, Hortobagyi Racka, Cikta, and Bábolna Tetra. Our results revealed that the indigenous Hungarian Hortobagyi Racka sheep are distinct from the other Hungarian breeds studied. The effective population sizes were found to be low, with varying levels of genomic inbreeding both within and across breeds. These results align with documented bottlenecks and instances of crossbreeding with other local or improved breeds. Ancestry analysis demonstrated some introgression between Scandinavian and Hungarian sheep breeds and vice versa. This gene flow may have occurred recently due to the widespread use of northern breeds such as Finnsheep and Romanov to enhance productivity, but it could also date back much further. Despite some limitations, our outcomes can contribute to future conservation plans, and a more comprehensive analysis of all native Hungarian sheep breeds should be highlighted to the relevant authorities in order to secure further funds.